ANALYSIS OF PROBLEM-SOLVING ABILITY: IMPLEMENTATION OF INQUIRY SOCIAL COMPLEXITY LEARNING MODEL AND SELF CONCEPT - Mara, Fera Kuspita; Supriadi, Nanang; Nabila, Siti Ulfa (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Mathematical problem-solving ability is an important ability for students to have, because if students' mathematical problem-solving ability is high, then students' self-concept is also high. This study aims to determine (1) the effect of the inquiry social complexity learning model on students' mathematical problem-solving abilities by controlling self-concept; (2) is there an influence of the self-concept covariate variable on students' mathematical problem-solving abilities; and (3) whether there is a simultaneous influence of inquiry social complexity and self-concept learning models on students' mathematical problem-solving abilities. The data analysis technique uses analysis of covariance (one-way ANCOVA) at a significance level of 5%. The research method used is quasi-experimental. The instrument used is in the form of tests and questionnaires, the type of test instrument is a test of mathematical problem-solving abilities, while the questionnaire instrument is a self-concept questionnaire. The results showed that (1) the mathematical problem solving abilities of students in classes treated with the inquiry social complexity learning model were better than students in classes treated with the conventional expository model; (2) the self-concept of students in the experimental class who were treated with the inquiry social complexity learning model and the control class who were treated with the conventional expository model had good scores, thus influencing students' mathematical problem solving abilities; (3) there is a simultaneous influence of the inquiry social complexity learning model and Self Concept on students' mathematical problem solving abilities. The results of the study indicate that students' mathematical problem solving and self-concept abilities can be improved by using the inquiry social complexity learning model.